The Hemoglobin Level as a Prognostic Factor in Patients with Non-Small Cell Lung Cancer Treated with Gemcitabine and cis-Platinum - Deyan N. Davidov (Peytchinski Publishing, 2012)
Objective: Anemia is observed in various malignancies including non- small cell lung cancer /NSCLC/ and is considered to be a poor prognostic factor. The aim of this study is to investigate whether there is a correlation between anemia, other clinic- pathological factors and survival in patients with advanced NSCLC treated with Gemcitabine / cis- Platinum- containing chemotherapy. Methods: Seventy eight consecutive patients with advanced NSCLC treated in Department of Chemotherapy, UMHAT - Dr. G. Stranski, Medical University - Pleven between 2006-2008 were retrospectively analyzed. Of those, 27 patients /34, 6%/ had low hemoglobin /HB/ level (<120g/L for men and <110g/L for women) prior to start chemotherapy. The HB levels were obtained at the time of their first visit to the hospital. All patients received chemotherapy regimen consists of intravenous administration of Gemcitabine 1250 mg/m2 day 1 and 8 and cis- Platinum 80mg/m2 day 1 with repetition over 21 days. Survival analysis was evaluated by Kaplan- Meier test. Results: The median survival time for all patients was 9,5 months. The median survival time for patients with low HB levels was 7,6 months versus 11,3 months in patients without anemia /p<0.05/. There was a significant correlation between anemia and clinical stage or performance status /p<0.05/.Conclusions: These results indicate that patients without anemia have significantly higher survival rate. Pretreatment HB level appears to be a useful prognostic indicator for survival in patients with inoperable NSCLC treated with chemotherapy.